Air quality assessment of industrial boilers exhaust and its impact upon workers' health - Khan, Adnan (2022)
Air pollution is a major concern worldwide with human activities being the main contributor and causing serious health impacts. The present study was designed to monitor the amount of gaseous pollutants (CO2, CO, SO2, NOX) and total suspended particulates (TSP) from different industrial boiler’s exhaust using three fuel types (coal, natural gas and heavy furnace oil/diesel). These five parameters were measured and compared with the National Environmental Quality Standards (NEQS) of Pakistan. Coal and diesel boilers were emitting more SO2 (22x) as compared to natural gas. The natural gas boilers were producing more CO (7x) due to inefficient combustion and low mixing of air into gaseous fuel. The concentration of NOx from all boiler types were within the standard value. TSP values ranged from 82.3 mg m-3 to 245.7 mg m-3, which were within the NEQS limits due to the presence of control devices. Workers’ health (n=42) was assessed using a questionnaire and health of many workers was found to be compromised (34 %), while most of them were either unaware or were not provided PPEs (37.5%). Consequently, the workers were being exposed to large amounts of hazardous emissions in the industry.